New comprehensive approach for airborne asbestos characterisation and monitoring - Klán, Miroslav; Pokorná, Petra; Havlíček, David; Vik, Ondřej; Racek, Martin; Plocek, Jiří; Hovorka, Jan (Environmental science and pollution research international, 2018)
High concentrations of airborne asbestos in the ambient air are still a serious problem of air quality in numerous localities around the world. Since 2002, elevated concentrations of asbestos minerals of unknown origin have been detected in the ambient air of Pilsen, Czech Republic. To determine the asbestos fibre sources in this urban air, a systematic study was conducted. First, 14 bulk dust samples were collected in Pilsen at nine localities, and 6 bulk samples of construction aggregates for gravel production were collected in a quarry in the Pilsen-Litice district. The quarry is the largest quarry in the Pilsen region and the closest quarry to the built-up urban area. X-ray diffraction of the asbestos minerals revealed that monoclinic amphibole (MA, namely actinolite based on subsequent SEM-EDX analysis) in the bulk samples accounted for < 1-33% of the mass and that the highest values were found in the bulk dust samples from the railway platform of the Pilsen main railway station. Simultaneously, 24-h samples of airborne particulate matter (PM) at three localities in Pilsen were collected. Actinolite was identified in 40% of the PM samples. The relationship between the meteorology and presence of actinolite in the 24 PM10 samples was not proven, probably due to the long sampling integration time. Therefore, highly time-and-size-resolved PM sampling was performed. Second, sampling of size-segregated aerosols and measurements of the wind speed (WS), wind direction (WD), precipitation (P) and hourly PM10, PM2.5 and PM1 were conducted in a suburban locality near the quarry in two monthly highly time-resolved periods (30, 60, 120 min). Three/eight PM size fractions were sampled by a Davis Rotating-drum Uniform-size-cut Monitor (3/8DRUM) and analysed for the presences of asbestos fibres by scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDX). Asbestos fibre detection in highly time-resolved PM samples and current WD and WS determination allows the apportionment directionality of asbestos fibre sources. The number of critical actinolite asbestos fibres (length ≥ 5 μm and width < 3 μm, 3:1) increased with the PM1-10/PM10 and PM2.5-10/PM10 ratios, WS > 2 m s-1 and precipitation < 1 mm. Additionally, the number of critical actinolite asbestos fibres was not related to a specific WD. Therefore, we conclude that the sources of airborne critical actinolite asbestos fibres in Pilsen's urban area are omnipresent. Frequent use of construction aggregates and gravel from the metamorphic spilite quarries in the Pilsen region and in many localities around the urban area is a plausible explanation for the omnipresence of the critical actinolite asbestos fibres concentration in Pilsen's ambient air. Mitigation strategies to reduce the concentrations of critical actinolite asbestos fibres must be developed. Continuous monitoring and performing SEM-EDX analysis of highly time-and-size-resolved PM samples, correlated with fast changing WS and WD, seems to be a strong tool for efficiently controlling the mitigation strategies of critical actinolite asbestos fibres.
Keywords: Actinolite asbestos; znečištění ovzduší; Air Pollution; DRUM sampler; Dust; SEM-EDX; azbest; velikost částic; prach; pevné částice; Česká republika; Microscopy, Electron, Scanning; Aerosols; aerosoly; Particle Size; látky znečišťující vzduch; Environmental Monitoring; Czech Republic; Air Pollutants; Asbestos; X-ray powder diffraction; monitorování životního prostředí; Naturally occurring asbestos; Particulate Matter; mikroskopie elektronová rastrovací